Keterlibatan Generasi Z dalam Aktivitas Olahraga Merupakan Tren Positif - Muksan Dali; Fadlun ch. Anwar; Gusti Randi Pakaya; Lina Putri Susanti Irawan; Meri Haryani (Universitas Negeri Padang, 2025)
This study aims to examine the involvement of students in sports activities at the Sports Coaching Education Study Program at Gorontalo State University and the factors that influence it. Generation Z in sports activities, the factors that influence it, and how sports become part of their lifestyle amidst academic, social, and technology pressures. The method used was a quantitative survey with a purposive sampling technique, involving 150 active students. The results showed that the majority of students participate in flexible sports such as running and gym training, influenced by social media and easy access to sports facilities. However, the main challenges faced are limited time due to academic workloads and a sedentary lifestyle. In conclusion, a technology-based approach and community support are needed to increase the consistency of sports participation among students. Requiring technology-based approaches and community support to increase the consistency of their participation in sports.